A new method for in situ structural investigations of nano‐sized amorphous and crystalline materials using mixed‐flow reactors. Issue 5 (23rd August 2019) - Hoeher, Alexandria; Mergelsberg, Sebastian; Borkiewicz, Olaf J.; Dove, Patricia M.; Michel, F. Marc
Abstract : A novel method is introduced for in situ X‐ray total scattering experiments. Two examples of the method as applied to non‐classical nucleation and crystal growth studies are discussed. Abstract : Structural investigations of amorphous and nanocrystalline phases forming in solution are historically challenging. Few methods are capable of in situ atomic structural analysis and rigorous control of the system. A mixed‐flow reactor (MFR) is used for total X‐ray scattering experiments to examine the short‐ and long‐range structure of phases in situ with pair distribution function (PDF) analysis. The adaptable experimental setup enables data collection for a range of different system chemistries, initial supersaturations and residence times. The age of the sample during analysis is controlled by adjusting the flow rate. Faster rates allow for younger samples to be examined, but if flow is too fast not enough data are acquired to average out excess signal noise. Slower flow rates form older samples, but at very slow speeds particles settle and block flow, clogging the system. Proper background collection and subtraction is critical for data optimization. Overall, this MFR method is an ideal scheme for analyzing the in situ structures of phases that form during crystal growth in solution. As a proof of concept, high‐resolution total X‐ray scattering data of amorphous and crystalline calcium phosphates and amorphous calcium carbonate were collected for PDF analysis.